Klasyka Weimarska — nie tylko męski fenomen kulturowy? - Małecki, Wiesław (Studia Europaea Gnesnensia, 2011)
The article is an attempt to take notice of and highlight the role of women in the making of the Germany’s one of a kind cultural phenomenon, the Weimar Classicism. This standpoint, insufficiently presented in Polish literature, is discussed more broadly on the example of three Weimar women from the times of Goethe: Princess Anna Amalia, Charlotta von Stein and Sophie von la Roche.